Professional communication of future doctors - Orel-Khaliq, Yuliya; Орел-Халік, Юлія Владиславівна (My University, 2021)
The article outlines that the development of specialized medical knowledge in harmony with professionally important personal qualities (moral, spiritual, ethical, communicative) gives the possibility to achieve the best results in professional training of medical staff. The effective formation of professional communication of medical students will make it possible to solve the contradictions between social, educational and professional training of specialists. The formation of culture of professional communication involves not only language education, which is aimed at the development of student's speaking competence but also at the development of general and professional culture. Future doctors should learn to find in each case such form of communication that should be suitable for the definite patient. professional communication.
Keywords: medical students; communicative culture; professional training